1990
DOI: 10.1128/jcm.28.1.148-149.1990
|View full text |Cite
|
Sign up to set email alerts
|

Rapid fluorescence method for screening Salmonella spp. from enteric differential agars

Abstract: Four hundred thirty-two lactose-negative colonies isolated from human feces on stool differential agar media were flooded with one drop of MUCAP Test reagent (Biolife Italiana S.r.I., Milan, Italy) and observed under a Wood lamp for the development of a blue fluorescence over or around the colony. On the basis of manual and automated conventional tests for the screening of Salmonella spp., the MUCAP Test yielded the following results: 79 true-positives, 314 true-negatives, 35 false-positives, and 4 false-negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 5 publications
3
8
0
Order By: Relevance
“…The PPV was also the highest with NBGL (61%), although if growth in SS or HE was combined with the C 8 -esterase test, the PPVs of these media rose to 100%. The usefulness of this test has already been established (1,10,17,18). The excellent performance of NBGL coincides with the results of Poisson and colleagues (11,13), which gave average sensitivities and PPVs higher than those of SS and HE.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The PPV was also the highest with NBGL (61%), although if growth in SS or HE was combined with the C 8 -esterase test, the PPVs of these media rose to 100%. The usefulness of this test has already been established (1,10,17,18). The excellent performance of NBGL coincides with the results of Poisson and colleagues (11,13), which gave average sensitivities and PPVs higher than those of SS and HE.…”
Section: Discussionsupporting
confidence: 79%
“…This substrate interacts with the Salmonella C 8 -esterase, leading to the release of umbelliferone, which is strongly fluorescent at 365 nm. A total of 5 l of the reagent was added to two to three suspect colonies, and the test was considered positive if a blue fluorescence of the colony was observed under a Wood lamp within 5 min (1,10,17,18). The cytochrome oxidase test was obtained from Difco.…”
Section: Methodsmentioning
confidence: 99%
“…The MUCAP test was found to be very sensitive, rapid and easy to perform but not very specific, due to the high number of false-positive results. This is in accordance with the findings of other researchers (Humbert et al 1989;Aguirre et a l . 1990;Betts and McGoldrick 1990).…”
Section: Resultssupporting
confidence: 94%
“…1990;Betts and McGoldrick 1990). The combination of the MUCAP test and selective media gives higher rates of specificity (Hurnbert et al 1989;Aguirre et al 1990). Since the most false-positive strains are cytochrome oxidase positive, the combination of MUCAP and cytochrorne oxidase test is recommended (Ruiz et al 1991).…”
Section: Resultsmentioning
confidence: 99%
“…No positive reaction occurred when 63 1-galnon-Salmonella members of the family Enterobacteriaceae were grown on Rambach agar. Conversely, other investigators (1) found 5 and 12% false-positive strains among the lactose-negative bacteria when they used Mac-Conkey and SS agars, respectively. However, we do not know which caprilate solvent they used.…”
mentioning
confidence: 85%